2014
DOI: 10.1177/2048872614534388
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of active Von Willebrand factor are increased in patients with first ST-segment elevation myocardial infarction: A multicenter and multiethnic study

Abstract: We found evidence that plasma levels of active VWF are an independent risk factor for first STEMI in patients from three different ethnic groups. Our findings confirm the presence of VWF abnormalities in patients with STEMI and may be used to develop new therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 39 publications
4
39
0
1
Order By: Relevance
“…The increase in VWF observed in our assay may mirror the in vivo effects seen in some of APS patients as they tend to have elevated levels of total and active VWF . Elevations of VWF in turn can lead to thrombotic events . Interestingly, the variation of VWF release induced by anti‐β2GPI antibodies from different patients suggests that elevations of VWF are not the sole driver of the prothrombotic state of APS and is consistent with the “multi‐factorial” activation hypothesis of APS.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The increase in VWF observed in our assay may mirror the in vivo effects seen in some of APS patients as they tend to have elevated levels of total and active VWF . Elevations of VWF in turn can lead to thrombotic events . Interestingly, the variation of VWF release induced by anti‐β2GPI antibodies from different patients suggests that elevations of VWF are not the sole driver of the prothrombotic state of APS and is consistent with the “multi‐factorial” activation hypothesis of APS.…”
Section: Discussionsupporting
confidence: 73%
“…While deficiency of VWF characterizes von Willebrand disease, elevations of VWF have also been implicated in thrombotic disorders, specifically cardiovascular disease, myocardial infarction, and arterial ischemic stroke. [12][13][14][15] The unique predisposition of APS to arterial stroke suggests that VWF, which has significant importance in arterial, platelet-rich thrombi, may play a role in the predisposition to thromboembolism seen in APS. Several reports have demonstrated an increase in cell surface VWF on endothelial cells treated with APL-Abs and higher levels of active VWF in the serum of patients with anti-β2GPI antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter and multiethnic study (China, Italy and Scotland) found that plasma levels of active VWF are an independent risk factor for first STEMI in patients, and confirm the presence of VWF abnormalities in patients with STEMI [55]. Consistent with such studies, the prevalence of cardiovascular diseases (CVD) in VWD patients is around half the prevalence of CVD in non-VWD patients [56].…”
Section: Vwf In Diseases Beyond Vwd and Ttpmentioning
confidence: 70%
“…More recently, in the ATHEROREMO-IVUS study [81], in patients with stable CAD (SCAD), an increased level of VWF:Ag was associated with higher coronary plaque burden, adverse CV outcome, and death during 1-year of follow-up. VWF is also an independent risk factor for first STEMI: levels of VWF are significantly increased in patients with first ST-elevation myocardial infarction (STEMI) rather than in controls [82]. Finally, Marcucci et al reported a possible relation between lower levels of ADAMTS13 and higher residual platelet reactivity (RPR), a marker of resistance to antiplatelet therapy associated with increased risk of ischemic events [83].…”
Section: Vwf In Metabolic and Cardiovascular Disease: Animal Modelmentioning
confidence: 99%